2012
DOI: 10.1021/jm201645r
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Design of Symmetrical Bis-benzimidazoles as Selective Inhibitors of the Trimethoprim-Resistant, Type II R67 Dihydrofolate Reductase

Abstract: The continuously increasing use of trimethoprim as a common antibiotic for medical use and for prophylactic application in terrestrial and aquatic animal farming has increased its prevalence in the environment. This has been accompanied by increased drug resistance, generally in the form of alterations in the drug target, dihydrofolate reductase (DHFR). The most highly resistant variants of DHFR are known as type II DHFR, among which R67 DHFR is the most broadly studied variant. We report the first attempt at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…Among these, the DfrB1 protein (also known as R67 DHFR) is the best-studied type II DHFR (13)(14)(15)(16)(17). It is proposed to be recently evolved, and it confers a significant survival advantage under TMP exposure to microbes that harbor it (18).…”
mentioning
confidence: 99%
“…Among these, the DfrB1 protein (also known as R67 DHFR) is the best-studied type II DHFR (13)(14)(15)(16)(17). It is proposed to be recently evolved, and it confers a significant survival advantage under TMP exposure to microbes that harbor it (18).…”
mentioning
confidence: 99%
“…Our results have direct implications on the threat that R67 DHFR holds with respect to antibiotic resistance. Already natively resistant to trimethoprim as a result of its fold being unrelated to that of DfrA DHFRs, R67 DHFR may continue to evolve even as we direct inhibitors to it, and will need to be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…20 Among the weakly inhibiting, low molecular weight fragments that were identified, 1 H -benzimidazole-5-carboxylic acid was selected to build symmetrical compounds that reflect the symmetry of the DfrB1 active site. 20 The resulting symmetrical bisbenzimidazoles offered competitive inhibition that was 100- to 1000-fold more efficient than the initial fragment, with K i in the low micromolar range (Scheme 1). 20 Preliminary crystallographic results and kinetic analyses demonstrated that two molecules of 1 bind simultaneously inside the DfrB1 tunnel.…”
Section: Introductionmentioning
confidence: 99%